2008
DOI: 10.1182/blood.v112.11.3666.3666
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Activated Natural Killer (NK) Cells from Myeloma Patients Kill Autologous Myeloma and Killing Is Enhanced by Elotuzumab

Abstract: Immune-based therapies may improve outcome for multiple myeloma (MM) by eradicating chemo-resistant disease. Our recent trial utilizing IL2 activated, killer immunoglobulin-like receptor-ligand mismatched NK cell transfusions from haplo-identical donors yielded (n) CR in 50% of patients. Unfortunately, after NK cell therapy, 2/10 patients had progressive disease, and the median duration of response for the other 8/10 patients was only 105 days (range 58–593). This may have been due to an insufficient dose of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In vitro studies have demonstrated that elotuzumab enhanced ADCC of autologous NK cells against primary MM cells from patients resistant to conventional or novel therapies. [8][9][10] Elotuzumab has also exhibited antitumor activity in human myeloma xenograft mouse models. 8,11 Elotuzumab has been combined with different classes of agents, some of which have been shown to enhance its ADCC activity in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have demonstrated that elotuzumab enhanced ADCC of autologous NK cells against primary MM cells from patients resistant to conventional or novel therapies. [8][9][10] Elotuzumab has also exhibited antitumor activity in human myeloma xenograft mouse models. 8,11 Elotuzumab has been combined with different classes of agents, some of which have been shown to enhance its ADCC activity in vitro.…”
Section: Introductionmentioning
confidence: 99%
“… 42 In a subsequent clinical trial on patients with high-risk relapsed/refractory MM, the infusion of high-dose ENK cells was safe and in vivo expansion was observed. 43 Pretreatment of autologous MM cells with elotuzumab could enhance ENK cell-mediated killing by ADCC in vitro, 44 providing the rationale for a combination therapy of elotuzumab and ENK cells. Elotuzumab was observed to be able to enhance both ENK cell-mediated, and to a much lesser extent, resting NK cell-mediated killing of autologous MM cells in vitro, implying that the activation status of NK effector cells contributes to elotuzumab activity ( Figure 3 ).…”
Section: Targeting Cs1 On Myeloma Cells With Elotuzumab-preclinical Smentioning
confidence: 99%